Exploring EFL Writing Teacher Confidence as A Response to Emergency Remote Teaching: A Preliminary Survey using TPACK Framework - Hanna Sundari; Fakhrurrazi M. Amin; Nur Syamsiah; Anita Anita (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
Online remote teaching has been implemented to curb the spread of corona virus (Covid-19) pandemic. Due to this unprecedented situation, EFL writing teachers should immediately adjust their teaching approaches through utilizing technology. Given the fact that the utilization of technology is ubiquitous in language teaching, rapid changing into full online teaching certainly brings some adaptations. Teachers have to handle full online learning and apply technology tools they apparently have never used before within a very short time preparation. This current study explored EFL writing teachers’ confidence, including their perceptions, in response to emergency remote teaching during Covid-19 pandemic as an initial survey. Twenty-two teachers who teach academic writing courses from nine universities in Indonesia took part in a survey through online questionnaire modified from EFL TPACK assessment by Baser, Kopcha, and Ozden (2016). Descriptive and thematic approaches were used as data analysis. The findings show that the EFL writing teachers’ confidence ranged between somewhat confident to fairly confident in the seven areas of technology, content, and pedagogy. They believe that competences they have are sufficient in managing online EFL academic writing course during emergency remote teaching. Nonetheless, when technology is integrated to other areas, the confidence levels seemingly decrease. Awareness of technical material and pedagogic technological knowledge received the lowest scores from all fields. Integration of technology in the process of language teaching, requires teachers to always improve their TPACK abilities through various ways, and this must also be supported by adequate facilities and infrastructure.